THE INFLUENCE OF EXTERNAL FACTORS ON ENTREPRENEURIALLY-ORIENTED E- COMMERCE ADOPTION IN MSMES: A CASE STUDY OF BALE BERDAYA SUMBAWA - Dira Meisyaqia; Zaenafi Ariani; Nur’aini Nur’aini; Mukhlishin Mukhlishin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of external factors on the adoption of entrepreneurially- oriented e-commerce among micro, small, and medium enterprises (MSMEs) of Bale Berdaya Sumbawa. Using a quantitative method with a sample of 100 MSME owners, data were collected through structured questionnaires and analyzed using multiple linear regression. The results show that external factors have a significant positive effect on entrepreneurially-oriented e-commerce adoption (p < 0.05), explaining 52.3% of the variance (R² = 0.523). Among the external factors examined, market demand and technological infrastructure demonstrated the strongest effects, with standardized beta coefficients of 0.421 and 0.367, respectively. These findings contribute theoretically by extending the understanding of e-commerce adoption through the lens of entrepreneurial orientation, highlighting how external stimuli interact with entrepreneurial behavior in digital contexts. Practically, the study offers actionable insights for policymakers, business support organizations, and digital platform providers to design interventions that enhance MSME competitiveness through targeted e-commerce strategies